Prevalence and risk factors of COPD among never-smokers in two areas of Sweden – Occupational exposure to gas, dust or fumes is an important risk factor. Issue 11 (November 2015) - Hagstad, Stig; Backman, Helena; Bjerg, Anders; Ekerljung, Linda; Ye, Xiong; Hedman, Linnea; Lindberg, Anne; Torén, Kjell; Lötvall, Jan; Rönmark, Eva; Lundbäck, Bo
Abstract: Background: Although active tobacco smoking is the main risk factor for COPD, COPD is not uncommon also among never-smokers. Different study locations along with different spirometric definitions of COPD have historically yielded different prevalence estimates of the disease. Aim: To study current prevalence and risk factors of COPD among never-smokers in two areas of Sweden. Methods: Data collected in 2008–2012 within the West Sweden Asthma Study and Obstructive Lung Disease in Northern Sweden Studies was pooled. The study population consisted of 1839 subjects who participated in spirometry and interviews. COPD was defined as post-bronchodilator a) FEV1 /(F)VC < 0.7, b) FEV1 /FVC < 0.7 and c) FEV1 /FVC < lower limit of normal. Results: Of the 1839 subjects, 967 (52.6%) were never-smokers. Among the never-smoking subjects, the prevalence of COPD according to definitions a–c was 7.7%, 4.9% and 3.0%, respectively. The corresponding prevalence of GOLD grade ≥2 was 2.0%, 1.4% and 1.3%. No significant difference in prevalence between the two study areas was observed. In never-smokers, occupational exposure to gas, dust or fumes (GDF) was significantly associated with both COPD (OR 1.85, 95% CI 1.03–3.33), and GOLD ≥2 (OR 4.51, 1.72–11.9) according to definition a), after adjusting for age, educational level and exposure to passive smoking at work. Conclusion: Depending on definition, prevalence of COPD among never-smokers was 3.0–7.7%, whereas GOLD ≥2 was present in 1.3–2.0%. Occupational exposure to GDF remained independently and significantly associated with COPD regardless of spirometric definition of the disease. Highlights: We examined risk factors and prevalence of COPD among never-smokers. Prevalence of COPD among never-smokers ranged from 3.0 to 7.7%, depending on definition. Occupational exposure to gas, dust or fumes was a significant risk factor.